Emerging Significance of Ginsenosides as Potentially Reversal Agents of Chemoresistance in Cancer Therapy - Xu, Jin-Feng; Wan, Yan; Tang, Fei; Chen, Lu; Yang, Yu; Xia, Jia; Wu, Jiao-Jiao; Ao, Hui; Peng, Cheng (Frontiers in Pharmacology, 2021)
Chemoresistance has become a prevalent phenomenon in cancer therapy, which alleviates the effect of chemotherapy and makes it difficult to break the bottleneck of the survival rate of tumor patients. Current approaches for reversing chemoresistance are poorly effective and may cause numerous new problems. Therefore, it is urgent to develop novel and efficient drugs derived from natural non-toxic compounds for the reversal of chemoresistance. Researches in vivo and in vitro suggest that ginsenosides are undoubtedly low-toxic and effective options for the reversal of chemoresistance. The underlying mechanism of reversal of chemoresistance is correlated with inhibition of drug transporters, induction of apoptosis, and modulation of the tumor microenvironment(TME), as well as the modulation of signaling pathways, such as nuclear factor erythroid-2 related factor 2 (NRF2)/AKT, lncRNA cancer susceptibility candidate 2(CASC2)/ protein tyrosine phosphatase gene (PTEN), AKT/ sirtuin1(SIRT1), epidermal growth factor receptor (EGFR)/ phosphatidylinositol 3-kinase (PI3K)/AKT, PI3K/AKT/ mammalian target of rapamycin(mTOR) and nuclear factor-κB (NF-κB). Since the effects and the mechanisms of ginsenosides on chemoresistance reversal have not yet been reviewed, this review summarized comprehensively experimental data in vivo and in vitro to elucidate the functional roles of ginsenosides in chemoresistance reversal and shed light on the future research of ginsenosides.